DETEKSI DINI PERKEMBANGAN ANAK USIA 48-72 BULAN DI TK AL AQSHA KOTA JAMBI TAHUN 2012 - Titik Hindriati (Universitas Batanghari Jambi, 2014)
Health development organized through the efforts of the health of children since the children still in the womb until the first five years of life . The results of the activities of the National Children 's Day celebration in 2010 of 500 children who were given only 476 child care SDIDTK ( Stimulation , Detection and Early Intervention Developmental ) and found 57 children ( 11.9 % ) with abnormalities of growth and development . Early detection activities need to be done early because it influences the risk of developmental disorders , both fine and gross motor development , hearing impairment , intelligence and speech delay .This study was conducted with the observation aims to describe the development of early detection of children aged 48-72 months in kindergarten Aqsa Jambi city in 2012 . Univariate analysis of the data . The population in this study were all children aged 48-72 months as many as 135 children with a total sample of 57 children . Stratified sampling technique that proppartional random sampling . The data used is primary data using observation sheets . Data retrieval on July 28 to August 5, 2011.The results showed 31 (54.4 %) of respondents have a corresponding development of ( S ) age , 15 (26.3 %) of respondents have doubts development (AD) and 11 (19.3%) of respondents detected deviation (P). Based on the results of the study indicate that the development of children aged 48-72 months who attend school in the kindergarten AL Aqsa most have appropriate growth and development and there is still detected irregularities growth. It is expected that the City of Edinburgh Aqsa kindergarten can perform monitoring / detection , stimulation and early intervention , especially in children whose growth is different from the others with its collaboration with stakeholders such as health centers . Keywords : growth and development and SDIDTK